QUILLBOT AS AN ALTERNATIVE WRITING TOOL: EXAMINING ITS USES ON THE ACADEMIC WRITING PERFORMANCE OF EFL LEARNERS - Yoandita; Yenni Hasnah (Universitas PGRI Palembang, 2024)
This study aimed to assess whether the use of QuillBot enhanced the academic writing skills of EFL learners in the English Education Department at Universitas Muhammadiyah Sumatera Utara. Pre-experimental design was implemented in this research. The participants in the research were selected from a class of 20 English as a Foreign Language (EFL) learners who had recently completed their academic writing classes the previous semester. Data from the pre-test and post-test was collected and a t-test was used for analyses using SPSS 29.0 version. This test consisted of an academic writing test about things that transpired in the educational sphere. The pre-test score reached 123, while the post-test score was 285. The data demonstrates that the t-test result was 56.53. The significance level of a = 0.05. The results determined that Sig (2-tailed) 0.000 is the probability value for the pre-test and post-test data for the EFL academic writing performance by using QuillBot. H0 is rejected since the probability (Sig.) 0.000 < 0.05. Furthermore, the results strongly indicate that QuillBot has greatly enhanced EFL learners' academic writing skills.